Sebuah Kerangka Teoretis Hubungan Institusional Berbasis Konstitusionalisme - Kurnia, Titon Slamet (Jurnal Hukum & Pembangunan, 2023)
This article discusses legal issue pertaining to institutional relationship between the Constitutional Court and the Supreme Court in case of constitutional interpretation, particularly the bindingness of the Constitutional Court’s opinion over the Supreme Court. Responding the issue, this article conveys departmentalist view, and rejects judicial supremacist view within the Constitutional Court in prescribing the constitutional interpretation authority. In line with departmentalism, this article argues that the Supreme Court should be given authority in constitutional interpretation, concurrent with the Constitutional Court. It is further argued that constitutional interpretation should be viewed as constitutional discourse in which the Supreme Court should be allowed to participate within its ratione materiae jurisdiction.